ДО ДИСКУСІЇ З ПРИВОДУ МІСТОБУДІВНИХ ПОВНОВАЖЕНЬ ОРГАНІВ МІСЦЕВОГО САМОВРЯДУВАННЯ - Околович, Марта Євгеніївна (SUPREMANCE OF LAW, 2017)
The article researches the history of development and formation of legal regulation of urban development in Ukraine from classical times to the late XIX century.